A Review on Beneficial Properties of Purple Okra - Chakraborty, Biswajit; Karak, Chandan; Maity, Ayantika; Marandi, Sanjita; Roy, Sourav; Pandit, Manas Kumar (International Journal of Economic Plants, 2024)
Okra is one of the most popular and commercially grown vegetables in different parts of the India due its nutritive, medicinal and economic value. Generally, green tender pods of okra are used as edible purpose and green varieties are commercially cultivated for most okra growing areas even export market also dominated by green varieties despite being the higher nutritive value of purple okra or red okra than green okra. Purple okra has enormous health benefits and can be used as traditional medicine in China and Indonesia. Several epidemiological studies proof superiority of purple okra over green okra due to presence of different types of antioxidants like beta-carotene, anthocyanin and phenolic compounds. Higher nutrients’ composition of purple okra can prevent some chronic diseases like goitre, diabetes, hyperlipidaemia, microbial infections, ulcers, and neurodegenerative diseases, irritation of the stomach and colon, gonorrhoea, sore throat, dysentery and also lower blood sugar. The fruits of purple okra have beneficial properties like anti-gastric acid, anti-oxidative, anti-fatigue, anti-inflammatory and even have insecticidal properties.